On the ultrasonic attenuation and its frequency dependence in the os calcis assessed with a multielement receiver - Strelitzki, R.; Metcalfe, S.C.; Nicholson, P.H.F.; Evans, J.A.; Paech, V. (Ultrasound in medicine & biology, 1999)
Measurements of broadband ultrasound attenuation (BUA) on a single sample using different devices have previously shown significant variations. We have used a new 3 × 3 array transducer to allow the evaluation of three new approaches to the BUA algorithms and the extent to which the variations might be reduced. Ten human os calces were measured using the array. The attenuation and its slope, the BUA, were calculated using three methods: 1. A phase sensitive approach, summing the individual signals from the multielement array in the time domain (TD); 2. a phase insensitive approach, summing the signals in the frequency domain (FD); 3. averaging of the individually measured attenuation and BUA values (AV). The TD and AV approaches resulted in slightly larger values for both attenuation (≈ 4%) and BUA (≈ 7%) than with the FD method. The differences between the TD and FD method may be due to phase cancellation. However, the three sets of results were not significantly different ( p < 0.05), which suggests that measurements on commercial equipment using large receiver apertures are not strongly affected by phase cancellation, averaging or scattering. Nevertheless, it is not clear if the differences observed are of clinical relevance, which should be investigated in the future. Our study shows that the 3 approaches are strongly related (r 2 ≥ 0.94), suggesting that translation may be possible between methods.